People's Perception Towards Wetland Culture: A Case Study of Dhimal Community, Nepal - Pokhrel, Puspa Lal (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
Dhimal is an indigenous community of Nepal, whose lifestyle is dependent on wetland. A large number of Dhimal are traditional inhabitants of wetland dominated Jungle area in the vicinity of a popular urban center of Tarai known as Damak. This paper attempts to highlight the linkage between wetlands and cultural practices of Dhimal in Eastern Tarai, Nepal. Likewise, their perceptions towards the wetland have also been studied. Damak was colonized by the Dhimal and Meche community during the 1860s to clear the Jungle. Dhimal communities have unique wetland related culture, rites and rituals. Their culture and way of life have been threatened after the 1950s when Nepal Malaria Eradication Organization was established. Before 1950 pestilence malaria was prevalent in Damak municipality. During that period the people of mountain and hilly region of Eastern Nepal did not dare to colonize Damak by clearing the jungle for cultivation. Until 1965, Damak was opulent and extremely rich in wetlands and wetlands resources. Sufficiency of wetland resources and way of life of Dhimal community had been delightful. In recent years their cultural practices are falling at risk due to shrinking and disappearances of wetlands.